2016
DOI: 10.1103/physreve.93.052609
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of open clusters of colloidal dumbbells via droplet evaporation

Abstract: We investigate the behavior of a mixture of asymmetric colloidal dumbbells and emulsion droplets by means of kinetic Monte Carlo simulations. The evaporation of the droplets and the competition between droplet-colloid attraction and colloid-colloid interactions lead to the formation of clusters built up of colloid aggregates with both closed and open structures. We find that stable packings and hence complex colloidal structures can be obtained by changing the relative size of the colloidal spheres and/or thei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…From the Einstein relation and the Stokes–Einstein equation for diffusion of spherical particles, we roughly estimate the physical time of the evaporation process to be on the order of seconds. For details of the calculation, see reference [11]. Although this physical time is quite small compared to experimental timescales that typically last tens of minutes, we do not expect the MC timescale to affect the final outcomes [25].…”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the Einstein relation and the Stokes–Einstein equation for diffusion of spherical particles, we roughly estimate the physical time of the evaporation process to be on the order of seconds. For details of the calculation, see reference [11]. Although this physical time is quite small compared to experimental timescales that typically last tens of minutes, we do not expect the MC timescale to affect the final outcomes [25].…”
Section: Model and Methodsmentioning
confidence: 99%
“…Peng and cowokers [10] prepared clusters of dumbbell-shaped particles and indicated that minimization of M2 is not a general rule for aggregation of shape-anisotropic particles. Open clusters with a compact core and protruding arms were obtained by varying the relative size of colloidal spheres in dumbbells [11]. Besides extending the colloidal shape, anisotropic surface chemistry has attracted considerable attention [12].…”
Section: Introductionmentioning
confidence: 99%